The effect of aerobic and resistance exercise training on the health related quality of life, physical function, and muscle strength among hemodialysis patients with Type 2 diabetes. Issue 2 (April 2020) - Jamshidpour, Boshra; Bahrpeyma, Farid; Khatami, Mohammad-Reza
Abstract: Introduction: Diabetic patients who undergo hemodialysis commonly suffer from reduction of both exercise capacity and muscle strength. These factors may have a negative effect on health related quality of life (HRQoL) and physical function. We investigated the effect of aerobic and resistance exercise training on the HRQoL, physical function, and muscle strength among hemodialysis patients with Type 2 diabetes. Methods: Twenty-eight diabetic patients who were on hemodialysis in the Milad Hospital (Tehran, Iran) were recruited for the study. Subjects were randomized into control (n = 13) and exercise training groups (n = 15). The exercise training group performed combined aerobic and resistance exercise training at moderate intensity (11–15/20 on the Borg scale) during hemodialysis treatment, 3 times a week for 8 weeks. The primary outcomes consisted of physical function measured by a 6-min walk test (6MWT), HR-QoL measured by the Short Form Health Survey (SF-36), and lower limb muscle strength measured using a hand-held Digital Dynamometer. Results: The 6MWT distance increased significantly in the exercise training group (36%). Bilateral hip flexor strength (right, 24.5%; left, 30.4%) and abductor strength (right, 27.6%; left, 25.2%) decreased significantly in the non-exercising control group but no significant change was found in the exercise group (P > 0.05). There were no significant changes in any of the 8 generic subscales of HR-QoL neither in the exercise training group nor controls following an 8- week study. Conclusions: 8 weeks of combined aerobic-resistance exercise training among diabetic hemodialysis patients seem to be effective in improvement of physical function and lower limb muscle strength.